Governance principles for community‐centered conservation in the post‐2020 global biodiversity framework. Issue 2 (8th January 2020) - Armitage, Derek; Mbatha, Philile; Muhl, Ella‐Kari; Rice, Wayne; Sowman, Merle
Abstract: Strategies to protect biodiversity in the face of a global crisis must be place‐based and sensitive to context. A failure to consider the socioeconomic and political circumstances, as well as wellbeing needs and lived realities of those most directly reliant upon biodiversity will further undermine progress on Aichi targets and subsequent goals for the post‐2020 framework. How communities experience the benefits or costs of conservation action is influenced in large measure by the principles that guide conservation governance, and the subsequent institutional structures and processes that frame conservation action (at local to global scales). In this article, we define and critically reflect on core principles of community‐centered conservation governance needed to yield desirable and long‐term conservation outcomes—both ecological and social (i.e., equitable and just). In doing so, we emphasize a conception of community‐centered conservation that we argue is relevant to guide implementation of a post‐2020 biodiversity framework, and which is based on a foundation of well‐established evidence. Core principles of community‐centered conservation governance include: (a) building multilevel networks and collaborative relationships needed to coproduce conservation solutions; (b) promoting equity and recognizing the central role of women as agents of positive change in conservation efforts across scales; (c) reframing conservation action through the lens of reconciliation and redress (e.g., responding to injustices from land grabs and territorial enclosures); (d) ensuring a rights‐based approach to conservation action in which community agency, access and decision making autonomy are supported; and (e) revitalizing the customary and local institutions that provide legitimate and adaptive strategies for the stewardship of biodiversity.